Relationship between soils and Amazon forest biomass: A landscape-scale study - Laurance, William F.; Fearnside, Philip Martin; Laurance, Susan G.W.; Delamônica, Patricia; Lovejoy, Thomas E.; Rankin-de Mérona, Judy M.; Chambers, Jeffrey Quintin; Gascon, Claude (Forest Ecology and Management, 1999)
Above-ground dry biomass of living trees including palms was estimated in 65 1 ha plots spanning a 1000 km2 landscape in central Amazonia. The study area was located on heavily weathered, nutrient-poor soils that are widespread in the Amazon region. Biomass values were derived by measuring the diameter-at-breast-height (DBH) of all ≥ 10 cm trees in each plot, then using an allometric equation and correction factor for small trees to estimate total tree biomass. Detailed information on soil texture, organic carbon, available water capacity, pH, macro- and micro-nutrients, and trace elements was collected from soil surface samples (0-20 cm) in each plot, while slope was measured with a clinometer. Biomass estimates varies more than two-fold, from 231 to 492 metric tons ha-1, with a mean of 356 ± 47 tons ha-1. Simple correlations with stringent (p < 0.006) Bonferroni corrections suggested that biomass was positively associated with total N, total exchangeable bases, K+, Mg2+, clay, and organic C in soils, and negatively associated with Zn+, aluminum saturation, and sand. An ordination analysis revealed one major and several minor soil gradients in the study area, with the main gradient discriminating sites with varying proportions of clay (with clayey soils having higher concentrations of total N, organic C, most cations, and lower aluminum saturation and less sand). A multiple regression analysis revealed that the major clay-nutrient gradient was the only significant predictor, with the model explaining 32.3% of the total variation in biomass. Results of the analysis suggest that soil-fertility parameters can account for a third or more of the variation in above-ground biomass in Amazonian terra-time forests. We suggest that, because the conversion of forest to pasture tends to reduce the nitrogen, clay, organic carbon, and nutrient contents of soils, forests that regenerate on formerly cleared lands may have lower biomass than the original forest, especially in areas with low soil fertility.
Keywords: Biomass; Estimation Method; Forest; Soil Fertility; Soil Nutrient; Soil-vegetation Interaction; South America